Anti-Synchronization of Fractional-Order Chaotic Circuit with Memristor via Periodic Intermittent Control - Fanqi Meng; Xiaoqin Zeng; Zuolei Wang; Xinjun Wang (Advances in Mathematical Physics)
In this paper, the anti-synchronization of fractional-order chaotic circuit with memristor (FCCM) is investigated via a periodic intermittent control scheme. Based on the principle of periodic intermittent control and the Lyapunov stability theory, a novel criterion is adopted to realize the anti-synchronization of FCCM. Finally, some examples of numerical simulations are exploited to verify the feasibility of theoretical analysis.